Wheat plant stature components - Scheeren, Pedro Luiz; Carvalho, Fernando I.F. de; Federizzi, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Wheat plant stature and its components were measured in non-segregated (P1, P2 and F1) and segregated (F2, RC1F1 and RC2F1) populations derived from crosses among different genotypes of wheat in field experiments carried out at the Agronomic Experimental Station/UFRGS, Guaíba, RS, in 1979. Internode patterns of both semi-dwarf and tall parents showed that: 1. Average internode lengths were progressively longer from the culm base to the spike; 2. A high portion of the phenotypic variation of the internode number was environmental in origin, and 3. The peduncle contributed with approximately 40% of the total stature of the genotypes.